2015
DOI: 10.1515/pjvs-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of P-glycoprotein in various subtypes of canine lymphomas

Abstract: Combination chemiotherapy is the current standard of care for dogs with lymphoma. Multidrug resistance is one of the most important factors contributing to the efficacy of chemiotherapy. The major protein responsible for this phenomenon is P-glycoprotein. Little is known about P-glycoprotein expression in particular subtypes of lymphomas. The aim of the study was evaluation of P-glycoprotein expression in various subtypes of canine lymphomas. Positive reaction with P-glycoprotein was found in 12/25 cases of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…High expression of ABCtransports and P-glycoprotein in particular, has been associated with a decreased response to cytotoxic drugs, and a poor prognosis in human malignant hematopoietic tumors [15]. We evaluated the Pgp expression in naturally occurring tumor cells by IHC as previously described in canine lymphoma [7,13,41,42] and the present study confirmed for the first time the superior antitumor activity of F14512 to etoposide phosphate in naturally occurring Pgp-overexpressing lymphomas in dogs. On the basis of these results, F14512 appears to be a potentially promising candidate for human clinical trials.…”
Section: Discussionsupporting
confidence: 67%
“…High expression of ABCtransports and P-glycoprotein in particular, has been associated with a decreased response to cytotoxic drugs, and a poor prognosis in human malignant hematopoietic tumors [15]. We evaluated the Pgp expression in naturally occurring tumor cells by IHC as previously described in canine lymphoma [7,13,41,42] and the present study confirmed for the first time the superior antitumor activity of F14512 to etoposide phosphate in naturally occurring Pgp-overexpressing lymphomas in dogs. On the basis of these results, F14512 appears to be a potentially promising candidate for human clinical trials.…”
Section: Discussionsupporting
confidence: 67%
“…In pretreated non-Hodgkin's lymphoma of humans, the reported incidence of Pgp staining varied from 2 to 49% in untreated patients and 64% in pretreated patients, while with mRNA analysis these figures were 22 ± 50% and 30 ± 60%, respectively (Sonneveld, 2000). Another report on dogs has documented that positive IHC reaction with Pgp was found in 12/25 (48%) cases of various morphological subtypes of lymphomas with < 10% cut-off value (Sokołowska et al, 2015), whereas Dhaliwal et al (2013) has reported that 19% of lymphoma cases were Pgp negative and 80% were Pgp positive with 50% cut-off value. These discrepant findings can be attributed to various factors such as stronger antigen retrieval in the current methodology, and also by the reasonably higher number of T-cell type (27.7%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on the evaluation of P-gp expression by immunohistochemistry [ 10 , 23 , 25 ], Western blotting [ 26 ], flow cytometry [ 28 , 53 ], and reverse transcription polymerase chain reaction (RT-PCR) [ 54 ]. Flow cytometry enables the evaluation of transporter function in single cells based on the efflux of fluorescent dyes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein (P-gp), a transmembrane glycoprotein that belongs to the ABC transporter superfamily, plays an important role in drug resistance by recognizing and extruding various chemotherapeutical molecules from cells [ 10 , 16 ]. P-gp is an independent prognostic factor in several human malignancies [ 17 , 18 ], and several studies suggest that it influences the treatment outcome of canine cancer including mast cell tumors [ 19 ], mammary tumors [ 20 ], pulmonary carcinoma [ 21 ], and lymphoma [ 22 , 23 , 24 , 25 ]. To estimate the P-gp levels, the expression can be quantified by immunohistochemistry [ 10 , 23 , 25 ], Western blotting [ 26 ], quantitative reverse transcription PCR (RT-qPCR) [ 27 ], or flow cytometry [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation